The Impact of Influencer Marketing, Online Customer Review, Brand Trust, Product Quality, and Price on Purchase Intention - Fariza, Aulia Farah; Wiyadi, W (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The beauty industry has experienced rapid growth in Indonesia. One of the well-known skincare brands in Indonesia is The Originote, which markets its products through the social commerce platform TikTok. The choice of The Originote is due to its ability to quickly penetrate the skincare market in Indonesia, facilitated by its diverse product offerings at affordable prices. The high demand for The Originote's products has prompted researchers to conduct a study on the variables that influence purchase intention for The Originote skincare products. This research aims to determine the impact of variables such as influencer marketing, online customer reviews, brand trust, product quality, and price on purchase intention. This study is quantitative research with a descriptive nature. Primary data was collected through online questionnaires and analyzed using SPSS software. A total of 103 respondents were obtained from students at Muhammadiyah University of Surakarta, using purposive sampling as non-probability sampling technique. Through regression analysis, the research results indicated that influencer marketing, online customer reviews, brand trust, product quality, and price have a positive and significant influence on purchase intention. The implications of this research are that the findings can serve as a reference for company management to collaborate with influencers to reach more potential customers and provide credible and easily accessible online product reviews. Consequently, brand trust will be established. Furthermore, companies should continue to deliver quality products while maintaining affordable prices.